Does education reduce the risk of hypertension? Estimating the biomarker effect of compulsory schooling in England - Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2010)
This paper estimates the exogenous effect of schooling on reduced incidence of hypertension. Using the changes in the minimum school-leaving age law in the United Kingdom from age 14 to 15 in 1947, and from age 15 to 16 in 1973, as sources of exogenous variation in schooling, the regression discontinuity and IV-probit estimates imply that completing an extra year of schooling reduces the probability of developing subsequent hypertension by approximately 7-12% points; the result which holds only for men and not for women. The correct IV-probit estimates of the LATE for schooling indicate the presence of a large and negative bias in the probit estimates of schooling-hypertension relationship for the male subsample.
Keywords: H1; I1; I2; 330; Hypertension; compulsory schooling; biomarker; regression discontinuity; health; Bildung; Herzkrankheit; Schulrecht; Schätzung; Großbritannien